Interleukin‐6 Receptor Blockade Enhances CD39+ Regulatory T Cell Development in Rheumatoid Arthritis and in Experimental Arthritis. Issue 2 (February 2014) - Thiolat, A.; Semerano, L.; Pers, Y. M.; Biton, J.; Lemeiter, D.; Portales, P.; Quentin, J.; Jorgensen, C.; Decker, P.; Boissier, M.‐C.; Louis‐Plence, P.; Bessis, N.
<x xml:space="preserve">Abstract</x> Objective The rationale for blocking interleukin‐6 (IL‐6) in rheumatoid arthritis (RA) lies chiefly in the proinflammatory effect of this cytokine. Few studies have evaluated the consequences of anti–IL‐6 receptor (IL‐6R) antibody treatment on Treg cells. This study was undertaken to elucidate the mechanism of action of anti–IL‐6R antibody treatment by studying the effects on Treg cells in an experimental arthritis model and in patients with RA. Methods Mice with collagen‐induced arthritis (CIA) were treated with a mouse anti–IL‐6R antibody (MR16‐1), and changes in Treg, Th1, and Th17 cells were assessed at key time points during the course of the disease. Peripheral blood from 15 RA patients was collected on day 0 and after 3 months of tocilizumab treatment for flow cytometry analysis of Th17 and Treg cells. Results In MR16‐1–treated mice, Th17 cell frequencies were unchanged, whereas Treg cell frequencies were increased. The Treg cell phenotype showed marked changes, with an increase in the frequency of CD39+ Treg cells in the lymph nodes and spleen. Interestingly, similar CD39+ Treg cell expansion was observed in RA patients who were tocilizumab responders at 3 months, with no change in Th17 cell frequency. Moreover, fluorescence‐activated cell–sorted CD39+ Treg cells from responder RA patients were functionally able to suppress the proliferation of conventional T cells. Conclusion In both CIA and RA, the frequency of functionally suppressive CD39+ Treg cells is increased as a result of anti–IL‐6R treatment, whereas Th17 cells are unaffected. The modification of Treg cell frequency and phenotype may be one of the mechanisms involved in the therapeutic effect of IL‐6 blockade in RA.